Preferred Academic Personality Traits for The Academic Staff Members from The Viewpoint of their Students - Tayoub, Mahmoud (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت الدراسة إلى تحديد السمات والمقومات الشخصية والأكاديمية والمهنية عند عضو الهيئة التدريسية في كلية الاقتصاد بجامعة تشرين من وجهة نظر طلابه. ولتحقيق ذلك تم إعداد وتوزيع استبيان على عينة من طلاب كلية الاقتصاد مؤلفة من 344 طالب وطالبة من مختلف المستويات والتخصصات للعام الجامعي 2006-2007.وخلصت الدراسة إلى النتائج الآتية: - ضرورة تحلي عضو الهيئة التدريسية بخصائص وسمات شخصية وأكاديمية ومنهية كنماذج معيارية ومقومات لأصول المهنة ولتقبل دوره ولمساعدته على التكيف الاجتماعي والأكاديمي مع طلابه. - أظهرت نتائج الدراسة والتحليل المتعدد المتغيرات وجود ثلاث مجموعات من السمات والمقومات يجب على عضو هيئة التدريس التحلي بها وهي: سلوكيات ومقومات شخصية – سلوكيات التفاعل الاجتماعي – سلوكيات أكاديمية ومهنية. This study aimed to identify the personality traits and characteristics for a university academic staff member at the Faculty of Economics, Tishreen University, from his students’ viewpoint. To check this, a questionnaire was prepared and distributed in Faculty of Economics students over a sample of 344 students (males and females) from different levels and specialties for the academic year 2006- 2007. The study ended with the following results: - An academic staff member should have standard personal, academic and professional traits as standard samples and criteria for the profession, in order that his role be accepted and help him adapt socially and academically with his students. The results of the questionnaire and multivariate analysis showed that there are three groups of traits and criteria a lecturer in a university should have, which are: personal behaviors and characteristics, social interaction behaviors, and academic and professional behaviors.